From post-industrial landscape to creative precincts: Emergent spaces in Chinese cities. - Hee, Limin; Schroepfer, Thomas; Su Nanxi; Li Ze (International Development Planning Review, 2008)
The urban development of Chinese cities has been very much a top-down process, leading to the oft-heard criticism that the current urban development process is overly influenced by national economic plans. This article attempts to unearth an emergent phenomenon in Chinese cities: post-industrial spaces that are initially revitalised by spontaneous occupation, later becoming established arts communities. These processes introduce important new spatial typologies and practices that have the potential to act as spaces of resistance to broad-brush planning by municipal authorities. The authors document the development of some of these spaces, and speculate on the role of artist-led gentrification and the development of new urban spaces in leading Chinese cities such as Shanghai and Beijing. The anatomy of these developments suggests how the face of bureaucratic Chinese planning has changed in the light of new challenges. Reprinted by permission of the publisher.